Constitutional Conscience and Plural Ethical Directionality. (2nd January 2022) - Chilton, Bradley S.; King, Stephen M.
Abstract : From the landmark work by John Rohr, Ethics for Bureaucrats, the authors seek to take a step in furthering moral readings of the Supreme Court for public administrators. While Rohr and the Constitutional School brought in constitutional case-law study, it doesn't seem to promote ethical reflection and has little impact on the growing crisis of ethics in public service. The paper posits a more systematic moral reading of constitutional law, developing an empirical, grounded understanding of teleological (utilitarian and virtue) and non-teleological (deontology) moral justifications in contemporary Supreme Court decisions on discrimination in public affairs. An applied plural ethical directionality model is constructed from this grounded, empirical approach to depict the content analysis of Court moral justification rhetoric, the overlapping nature of moral justification types, and cleavages. The contemporary Court usually employs teleological utilitarian moral justifications in its opinion-writing, with non-teleological moral justifications only in some cases of majoritarian injustice. Virtue moral justifications are rarely found–speculated in cases of segregation–and only hinted with litigants of bad character. The applied plural ethical directionality model suggests predictable choices for moral justifications.